Comparison in Statistical Market Analysis Method Used for Real Estate Valuation in Poland - Konowalczuk, Jan (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
In Poland, the statistical market analysis method (SMAM) is a comparative approach. This classification differs from the real estate valuation theory and practice employed in mor developed markets, e.g. in the US. This real estate valuation method does not involve making comparisons that would reflect the behaviour of market participants. The aim of this article is to evaluate SMAM in connection with the comparative method applied in economics and in relation to real estate valuation theory and practice, taking into account current judicial rulings, and to present an outline of the development of this method in Poland. The article is based on studies of domestic and foreign literature, a comparative study of Polish and American methodology, and a critical analysis of judicial rulings. The author proposes that SMAM be excluded from the comparative approach, which is designed to determine the market value of individual properties and be used instead to valuate real estate for tax purposes.